2016
DOI: 10.1117/1.jrs.10.036015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of partial least squares and support vector regressions for predicting leaf area index on a tropical grassland using hyperspectral data

Abstract: .Leaf area index (LAI) is a key biophysical parameter commonly used to determine vegetation status, productivity, and health in tropical grasslands. Accurate LAI estimates are useful in supporting sustainable rangeland management by providing information related to grassland condition and associated goods and services. The performance of support vector regression (SVR) was compared to partial least square regression (PLSR) on selected optimal hyperspectral bands to detect LAI in heterogeneous grassland. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
1
27
0
2
Order By: Relevance
“…Beyond individual vegetation attributes, PLSR was recently used to predict landscape-scale fluxes of net ecosystem exchange (NEE) and gross primary productivity (GPP) across multiple timescales (Matthes et al 2015), and also for the estimation of floristic composition of grassland ecosystems (Harris et al 2015;Neumann et al 2016;Roth et al 2015). At the same time, thanks to its PLS-vectors, PLSR is also increasingly applied for band sensitivity analysis of spectroscopic datasets in view of the targeted application (e.g., Feilhauer et al 2015;Kiala et al 2016;Kira et al 2016;Li et al 2014a;Neumann et al 2016). Various experimental studies demonstrated the superior predictive power of PLSR as opposed to VIs for the prediction of multiple vegetation properties, including above-ground biomass, LAI, leaf pigments (chlorophyll, carotenoids), GPP and NEE fluxes, leaf rust disease detection and nutrients concentration (nitrogen and phosphorus concentrations) (Capolupo et al 2015;Dreccer et al 2014;Foster et al 2017;Hansen and Schjoerring 2003;Matthes et al 2015;Wang et al 2017a;Yue et al 2017).…”
Section: Linear Nonparametric Methodsmentioning
confidence: 99%
“…Beyond individual vegetation attributes, PLSR was recently used to predict landscape-scale fluxes of net ecosystem exchange (NEE) and gross primary productivity (GPP) across multiple timescales (Matthes et al 2015), and also for the estimation of floristic composition of grassland ecosystems (Harris et al 2015;Neumann et al 2016;Roth et al 2015). At the same time, thanks to its PLS-vectors, PLSR is also increasingly applied for band sensitivity analysis of spectroscopic datasets in view of the targeted application (e.g., Feilhauer et al 2015;Kiala et al 2016;Kira et al 2016;Li et al 2014a;Neumann et al 2016). Various experimental studies demonstrated the superior predictive power of PLSR as opposed to VIs for the prediction of multiple vegetation properties, including above-ground biomass, LAI, leaf pigments (chlorophyll, carotenoids), GPP and NEE fluxes, leaf rust disease detection and nutrients concentration (nitrogen and phosphorus concentrations) (Capolupo et al 2015;Dreccer et al 2014;Foster et al 2017;Hansen and Schjoerring 2003;Matthes et al 2015;Wang et al 2017a;Yue et al 2017).…”
Section: Linear Nonparametric Methodsmentioning
confidence: 99%
“…There are two main approaches to build LAI estimation models from remote sensing data; the empirical statistical approach and the radiative transform model (RTM) approach [8]. The former approach includes univariate regression models built on a vegetation index (VI) and multivariate-calibration-based models using the full reflectance spectrum [14][15][16]. These multivariate calibration techniques include the partial least squares regression (PLSR) methods and modern machine learning methods such as support vector regression (SVR), random forests (RF), and artificial neural networks (ANN).…”
Section: Introductionmentioning
confidence: 99%
“…PLSR has been considered to be a powerful alternative to univariate methods and provides better performance in most cases [27][28][29], although there is a study that reported the opposite results [22]. Moreover, the potential performance of the state-of-the-art machine learning methods, such as SVR, RF and ANN, has been explored in several studies [14,15,30]. These studies showed that the state-of-the-art machine learning techniques appear to be more efficient than the VI and PLSR methods in most LAI estimation cases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations